Meminimalkan Kelelahan dan Meningkatkan Produktivitas dengan Pendekatan Metode Failure Mode and Effect Analysis (Studi Kasus: PT. Kubota Indonesia) - Antoni Yohanes; Ahmad Karsim (Jurnal Serambi Engineering, 2025)
In the context of increasing globalisation and the implementation of the ASEAN Economic Community (AEC), Indonesian companies are under pressure to improve their collective productivity and efficiency. Although the integration of advanced technology is the main focus, human involvement still plays a crucial role in achieving optimal production. This research examines the factors contributing to worker fatigue during material handling activities, emphasising the importance of prioritising employee well-being, safety, and health. A proven effective approach is to take an ergonomic design approach to workstations to suit the physical characteristics of workers, thereby reducing fatigue levels and increasing productivity. Implementing the Failure Mode and Effects Analysis (FMEA) method is proposed as a systematic way of identifying and addressing various operational challenges. A case study at PT Kubota Indonesia demonstrates that implementing this method can significantly enhance manufacturing productivity while maintaining stringent safety standards.